Sport activities and EDs - Corvino, Isabella (Eracle. Journal of Sport and Social Sciences, 2023)
The aim of these articles is to approach the theme of Eating Disorders (EDs) connected with sport activities. Sports activity remains an open field: it is not in itself didactic nor does it necessarily represent a positive experience. In sport, themes such as identity, relationships, health, are strictly bonded to self-realization, social pressure on performance and desirable beauty standards; this partially poisoned the sport environment. The spectacularized and consumerist form of these activities - mostly linked to social distress and the communication world -, the way to perfection storytelling can sometimes bring out disorders or even there can be the case in which people use sport to hide the disorder behind strict health protocols. We need to focus a more cautious look on sport so that it can be filled with positive meanings linked to the emancipation of oneself, to a playful dimension as fun and pleasure, to educational paths, free expression and equality.